THE LIMITATIONS OF RELIGIOUS PRACTICES IN POLISH PRISONS - Zawiślak, Michał (Review of European and Comparative Law, 2017)
The subject of this article is the issue of religious fredom of prisoner in the light of limitations of religious practices. The article presents legal and sociological status of religious assistance in contemporary Polish prisons. The aim of the paper is to analyze the prisoner’s situation based on selected case law. Religious practices seem to be important part of long process of resocialization of the prisoners, but still prison staff is not prepared to ensure the perform religious practices in right manner. It needs to be stressed that religious practices are subject to limitations in prisons. The article focus on typical problems arising from lack of detailed internal prison policy regulations.